2006
DOI: 10.1103/physrevb.74.054432
|View full text |Cite
|
Sign up to set email alerts
|

Nonextensivity in magnetic nanoparticle ensembles

Abstract: A superconducting quantum interference device and Faraday rotation technique are used to study dipolar interacting nanoparticles embedded in a polystyrene matrix. Magnetization isotherms are measured for three cylindrically shaped samples of constant diameter but various heights. Detailed analysis of the isotherms supports Tsallis' conjecture of a magnetic equation of state that involves temperature and magnetic field variables scaled by the logarithm of the number of magnetic nanoparticles. This unusual scali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Indeed, the correctness of the scaling appearing in Eq. (9) for nonstandard systems, i.e., for those with θ = 0, has been profusely verified for several systems in the literature [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; one of them is going to be discussed in Section 4 below. Furthermore, it has been shown that such scalings preserve important thermodynamical relations such as the Euler and Gibbs-Duhem [21].…”
Section: Why Should the Thermodynamical Entropy Always Be Extensive?mentioning
confidence: 89%
“…Indeed, the correctness of the scaling appearing in Eq. (9) for nonstandard systems, i.e., for those with θ = 0, has been profusely verified for several systems in the literature [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; one of them is going to be discussed in Section 4 below. Furthermore, it has been shown that such scalings preserve important thermodynamical relations such as the Euler and Gibbs-Duhem [21].…”
Section: Why Should the Thermodynamical Entropy Always Be Extensive?mentioning
confidence: 89%
“…The samples creating the m vs. T data shown in Fig. 18 142 From measurements like these ZFC/FH and FC m vs. T curves together with magnetic isothermal m vs. H measurements and the investigation of thermoremanent magnetization one can determine information such as the nanoparticle number, the moment per particle, and some qualitative estimates of the anisotropy energy which determines the blocking temperature of the nanoparticle ensemble.…”
Section: Squid Magnetometry In Magnetic Nanoparticle Characterizationmentioning
confidence: 99%
“…18 shows a prototypical magnetometric investigation of nearly interaction free g-Fe 2 O 3 nanoparticles which have been randomly dispersed in a polystyrene matrix. 142 The particles were produced by a synthetic strategy, more specifically, via thermal decomposition of metal carbonyls in the presence of appropriate surfactants. 82,145,146 The procedure is known to result in highly uniform nanoparticles.…”
Section: Squid Magnetometry In Magnetic Nanoparticle Characterizationmentioning
confidence: 99%
“…The curves in Figure 8 show a significant increase in the magnetic properties with an increase in the concentration of Ni or Co and a behavior similar to superparamagnetic behavior, typical of metal nanoparticles. [ 66 ]…”
Section: Resultsmentioning
confidence: 99%